1997
DOI: 10.1007/bf02845211
|View full text |Cite
|
Sign up to set email alerts
|

End tidal carbon dioxide monitoring—Its reliability in neonates

Abstract: End tidal Carbon dioxide monitoring was undertaken prospectively in all Ventilated neonates in our NICU admitted from March 1995 to August 1995 irrespective of the birth weight, gestational age and indication of ventilation. The aim was to determine the correlation between ETCO2 and PaCO2 in various clinical situations. The arterial blood gases were obtained in all ventilated babies with simultaneous and continuous ETCO2 monitoring and were analysed by AVL 995 Hb blood gas analyser. ETCO2 was analysed by side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
(2 reference statements)
0
17
0
1
Order By: Relevance
“…An intraclass correlation coefficient (ICC) of 0.60 for CO 2 assessment by PetCO 2 or TcPCO 2 compared to PaCO 2 measurement for preterm infants has been reported in a previous study. 5 A total of 27 preterm infants were required to demonstrate an agreement level of 0.80 at a 5% type I error and 20% type II error at any time of sampling. 13 Bland Altmann analysis was used to determine precision and bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intraclass correlation coefficient (ICC) of 0.60 for CO 2 assessment by PetCO 2 or TcPCO 2 compared to PaCO 2 measurement for preterm infants has been reported in a previous study. 5 A total of 27 preterm infants were required to demonstrate an agreement level of 0.80 at a 5% type I error and 20% type II error at any time of sampling. 13 Bland Altmann analysis was used to determine precision and bias.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive monitoring of carbon dioxide such as transcutaneous partial pressure of carbon dioxide (TcPCO2) and partial pressure of end-tidal carbon dioxide in the expired air (PetCO 2 ) have shown usefulness in adults, children and full-term neonates. [1][2][3][4][5][6][7][8][9] These methods offer the advantages such as simplicity, reduction in blood sampling and incidence of iatrogenic anemia and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of out-of-range Pa CO 2 values was not reduced, ET CO 2 was lower during ventilation than during breathing [95]. While studies in the neonatal intensive care unit have found that ET CO 2 closely correlates with Pa CO 2 [96,97,98], it is important not to extrapolate these findings to the situation in the delivery room, when the lung is partially liquid filled. The assumption that ET CO 2 will approximate Pa CO 2 levels relies on the fact that CO 2 exchange in the lung is not diffusion limited.…”
Section: Measurements For Evaluating Transitionmentioning
confidence: 96%
“…Gas exchange measurements during transition, using capnography, could assist in defining adequate tidal volumes [96,97,98] and the total amount of proper gas exchange. However, this technique can be influenced by other variables such as mask leak and the dead space of the mask and sensor.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Four (n=723) assessed end-tidal CO 2 , one assessed transcutaneous CO 2 (n=46) and one assessed both (n=37). (41)(42)(43)(44)(45)(46) The correlation between blood CO 2 and noninvasive monitoring was acceptable (correlation coefficient 0.55 to 0.82). In infants with significant pulmonary disease, the end-tidal CO 2 partial pressure of CO 2 may be quite discrepant due to large dead space volumes.…”
Section: Does the Use Of Noninvasive Monitoring Inmentioning
confidence: 90%